Category of “property” and subjects of property rights protection of the echr - Abroskin, V. V.; Andreichenko, S. S.; Bogdan, V. V.; Chebotareva, G. V.; Kizlova, O. S. (Lviv-Toruń : Liha-Pres, 2019)
So, since the ideology of article 1 of the First Protocol is actually reflected in the Constitution and the Civil code of Ukraine, the national courts should take into account legal positions of the ECHR in disputes on protection of property rights, to refer to the conclusions of the ECHR as a direct source of law, and to adopt in its decision the idea of justice and humanity.
Kizlova O. S. Category of “property” and subjects of property rights protection of the echr. Theoretical and practical problems of the legal regulation of social relations : collective monograph / V. V. Abroskin, O. S. Kizlova, S.S. Andrichenko, V.V. Bogdan, G.V. Chebotareva, etc. Lviv-Torun : Liha-Pres, 2019. - PP. 127-143.
Keywords: substantive composition of the applicants to the ECHR; the concept of property rights in the attitude of the ECHR